KERETA SINGO BARONG DI KERATON KASEPUHAN CIREBON - Sumino Sumino (Institut Seni Indonesia Yogyakarta, 2012)
This study to look at the changes the meaning of Singo Barong in the context of the past asunderstood by the public Cirebon in the present. In the time, the train experienced a period oftransit which to change the context in which the material or object of art will have meaning.As a result of the frequent occurrence of changes in the context of the meanings are oftensubject to change. It is an art object in transition, experiencing a change of meaning as aresult of changes in context. Change of meaning will evoke an emotional response whencrossing cultural boundaries.Reading of documents or artifacts that are relevant necessary to achieve a deeper meaningand detail. Therefore anthropological perspective that links production and consumption ofartifacts are not separated from the question of the culture, politics, religion and others.Borrowing the theory of